Sovereign green bond reporting practices in the EU: a harmonised or fragmented landscape? - Lukács, Bence (Cognitive Sustainability, 2025)
In order to meet the growing funding needs of green transition in the European Union, member states started issuing green bonds. On the green bond market, sovereigns are expected to report on the use of the green bond proceeds and their impact. Several voluntary guidelines are available for green bond reporting on the market, including the International Capital Market Association Green Bond Principles (ICMA GBP) or the European Union Green Bond Standard (EuGBS), which is based on the EU Taxonomy. This study provides an overview on the current sovereign green bond reporting practices in the EU, taking into account their most recent green bond reports and related documents (green bond frameworks, external reviews etc.). The results show that all sovereigns in the EU implement the ICMA GBP, while many strive to comply with the criteria of the EU Taxonomy and EuGBS on a best effort basis. Due to the voluntary use of the standards, the reporting practices among sovereigns greatly vary: each country uses its own approach for EU Taxonomy assessment, allocation and impact reporting, which leads to market fragmentation and limited comparability of the sovereign green bonds. The EuGBS could create a common ground for reporting requirements by strengthening comparability and credibility and improving the transparency on the market. However, due to its strict requirements such as the alignment with the EU Taxonomy, it is complicated for sovereigns to comply with the standard.